Dried Human Amniotic Membrane Does Not Alleviate Inflammation and Fibrosis in Experimental Strabismus Surgery - Bo Young Chun; Hong Kyun Kim; Jae Pil Shin (Journal of Ophthalmology)
Purpose. The purpose of this study was to evaluate the efficacy of dried human amniotic membrane (AM) in reducing the postoperative inflammatory response and scarring after strabismus surgery. Methods. The inflammatory response at the extraocular muscle reattachment site was analyzed after superior rectus (SR) resection in 12 rabbits. Dried human AM (Ambiodry2) was applied between the resected SR muscle plane and Tenon’s capsule of the left eyes of rabbits. As a control, the right eyes of rabbits underwent SR resection only. The surgeon randomly ordered which eye gets operated first during the experiment. Two weeks later, enucleation was performed. Six sagittal sections were made for each eye at the insertion of the SR muscle. The grade of postoperative inflammation and the presence of fibrosis were evaluated in histological examinations. Results. There was no statistically significant difference in the intensity of inflammation and fibrous proliferation between the eyes treated with dried human AM after SR resection and those treated with SR resection only. Conclusions. The use of dried human AM was not effective in controlling the postoperative inflammation and scarring in rabbit eyes after extraocular muscle surgery. However, this may be due to the devitalized dry preparation of human AM (Ambiodry2), which may have lost the expected anti-inflammatory and anti-scarring properties, and further studies on humans may be necessary.